EFFECT OF STERILIZATION BY HEATING IN THE PRESENCE OF BACTERICIDE AND BACTERIAL FILTERED MEMBRANE ON THE STABILITY OF EYE DROPS CONTAINING 0.5% CHLORAMPHENICOL AT VARIOUS pH - FITRI KUSUMA, SRI AGUNG; ABDASSAH, MARLINE (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of this study was to determine a sterile 0.5% chloramphenicol eye drop formula with the best potency of antibacterial by determining the appropriate sterilization method and the supporting pH. Methods: 0.5% chloramphenicol was formulated with 0.01% thimerosal, which act as a bactericide and combines with borate buffer to produce eye drop formulas with variations in pH (6.8, 7.0 and 7.4). All formulas were stored at room temperature for 28 d and were evaluated, including: organoleptic of the preparations, sterility, pH stability, and the antibacterial potency of chloramphenicol in eye drops. Results: All dosage formulas did not undergo photodegradation reactions which were marked by no change in color until the end of the storage period. However, the formula with pH 6.8 which was sterilized by heating in a presence of bactericide, showed the presence of more particulate precipitates than in the pH 6.8 formula which was sterilized using membrane filter bacteria. However, both methods of sterilization produced sterile chloramphenicol eye drops. The preparation using a method of heat sterilization with bactericide decreased the pH greater than the preparation using a sterile bacterial filter sterilization method. C2 preparations at pH 7.0 and sterilized using the bacterial filter membrane sterilization method were more stable because they had the smallest pH change of 0.05 and the percentage reduction in antibacterial potential was smaller at 1.15%. Conclusion: The best treatment for the chloramphenicol eye drop was kept the pH formula at pH 7 and sterilized using bacterial filter membrane sterilization method.